Synthesis of unusual isoxazoline containing β and γ-dipeptides as potential glutamate receptor ligands1. Issue 7 (8th July 2015) - Tamborini, Lucia; Mastronardi, Federica; Dall'Oglio, Federica; De Micheli, Carlo; Nielsen, Birgitte; Lo Presti, Leonardo; Conti, Paola; Pinto, Andrea
<x xml:space="preserve">Abstract</x> Unconventional beta and gamma dipeptides as tools to investigate the iGluR binding domain.